2019
DOI: 10.1074/jbc.ra119.011009
|View full text |Cite
|
Sign up to set email alerts
|

Meclofenamic acid promotes cisplatin-induced acute kidney injury by inhibiting fat mass and obesity-associated protein-mediated m6A abrogation in RNA

Abstract: The role of RNA methylation on the sixth N atom of adenylate (m 6 A) in acute kidney injury (AKI) is unknown. FTO (fat mass and obesity-associated protein) reverses the m 6 A modification in cisplatin-induced AKI. Here, we aimed to determine FTO's role in AKI. We induced AKI in c57BL/6 mice by intraperitoneal cisplatin injection and treated the animal with vehicle or an FTO inhibitor meclofenamic acid (MA) for 3 days. Moreover, as an in vitro model, human kidney proximal tubular cells (HK2 cells) were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 16 publications
2
46
0
Order By: Relevance
“…Therefore, we chose 100μM MA1 by CCK8 cell viability test to reduce the side effect of MA1 on RPE cells (Figure 3a and b). Previous study showed that MA could effectively inhibited FTO's function and expression, in uencing its downstream pathways [35]. In our study, we used MA1 to inhibit FTO demethylation in Aβ induced damaging model.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, we chose 100μM MA1 by CCK8 cell viability test to reduce the side effect of MA1 on RPE cells (Figure 3a and b). Previous study showed that MA could effectively inhibited FTO's function and expression, in uencing its downstream pathways [35]. In our study, we used MA1 to inhibit FTO demethylation in Aβ induced damaging model.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, a novel study supported that silencing METTL3 could inhibit apoptosis in hypoxia/reoxygenation-treated cardiomyocytes [37]. Overexpression of METTL3 or knockdown of FTO enhanced m 6 A levels and activated apoptosis in cisplatin-treated human kidney proximal tubular cells [38]. Conversely, METTL3 knockdown could active caspase-3 in gastric cancer cells [39].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that m6A modification can regulate cellular responses to stimuli by affecting mRNA transcription, splicing, localization, translation, stability, and posttranscriptional regulation of gene expression at the RNA level (Zhou et al, 2015;Fry et al, 2017). Evidence (Anders et al, 2018;Wang Y. et al, 2019;Zhou P. et al, 2019;Li et al, 2020;Liu et al, 2020;Xu et al, 2020) also suggests a strong relationship between m6A modification and kidney disease, thereby revealing an important biological role for m6A in the regulation of kidney injury. In this study, a reliable cisplatin-induced AKI model was established in mice, and the model was tested by analyzing Scr, BUN, and kidney section images.…”
Section: Discussionmentioning
confidence: 96%
“…Another study reported that cisplatin treatment reduced FTO expression and increased m6A levels in vivo and in vitro. They also found that inhibiting FTO by meclofenamic acid aggravated renal damage and increased apoptosis in cisplatin-treated kidneys (Zhou P. et al, 2019). METTL14 is elevated in people with AKI (Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 97%